Infective Endocarditis: A Multidisciplinary Interactive Team-Based Learning Exercise - Stuart Nelson (Association of American Medical Colleges, 2006)
Abstract Introduction This educational resource is a team-based exercise centering on a case of infective endocarditis due to viridans streptococci. These bacteria gained access to the patient's blood following trauma to the mouth and teeth inflicted by a baseball bat during a barroom brawl. The patient presents with a fever, facial bruise, heart murmur, subungual splinter hemorrhages, Roth spots, and splenomegaly. Methods The exercise is a PowerPoint presentation organized as an unfolding case history. Presenting the slides in sequence allows the case to unfold over time. Eight multiple-choice questions are inserted at strategic points in the exercise. Medical students may answer these questions in teams or as individuals. In attempting to answer these questions, the student or teams of students should have access to reference books, a medicine textbook, and a medical dictionary. The exercise works best if it is not distributed to medical students in paper form at the beginning of class or ahead of time. Instead, the PowerPoint presentation should be projected on a screen and allowed to unfold one slide at a time. This exercise typically requires 75-90 minutes. Results We have field-tested this exercise for 3 years (in 2003, 2004, and 2005) as part of a module in the second-year curriculum's cardiovascular course at the Wright State University Boonshoft School of Medicine. Suggestions for improvement from students and faculty have been incorporated to enhance the exercise's quality. Discussion Use of this exercise encourages collegial interaction, peer-to-peer clarification of knowledge, and dynamic sharing to arrive at consensus choices. The slide-by-slide presentation mimics real life, and our experience has confirmed the effectiveness of this strategy. When presenting the case to students, it is important to use a title that does not reveal which disease(s) the patient has. The case is suited for use as a team-based learning application exercise in which students reach consensus and then vote as a team. Use of timers and audience response technology may enhance the administration of this resource.